Polemics on Acknowledgement of N. Copermcus’ System in Lithuanian Schools in the Second Half of the 18th Century - Plečkaitis, Romanas (Problemos, 1968)
In the second half of the 18th century some philosophers, teaching at Lithuanian schools, proposed to keep to the system of Tycho Brahe, while others delivered Copernicus’ system, but only as a hypothesis. Dionysius, professor of philosophy at the Vilnius Trinitarian College, presented Copernicus’ system not as a hypothesis but as an established fact. Dionysius explained the Scripture in accordance with the propositions of Copernicus’ system.